2019
DOI: 10.51985/jbumdc2019086
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Rehabilitation and Constraint Induced Movement Therapy on Brain Derived Neurotrophic Factor Mediated Motor Improvement in Stroke Patients

Abstract: Objectives: To carry out a comparison between serum BDNF levels as well as enhancement in upper limb motor function in terms of gross movement, pinch, grip, primary grasp, pre and post intervention in the study and control groups. Study design And Setting: It was a Randomized Control Study conducted from March 2015 to March 2016 at Holy Family Hospital Rawalpindi in collaboration with the Multidisciplinary research laboratory at Islamic International Medical College, Rawalpindi. Methodology: In this study; for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…No subgroup differences were detected. Sensitivity analysis showed that the study of Anjum et al [ 84 ] was influential (Additional file 12 : Fig. S12).…”
Section: Resultsmentioning
confidence: 99%
“…No subgroup differences were detected. Sensitivity analysis showed that the study of Anjum et al [ 84 ] was influential (Additional file 12 : Fig. S12).…”
Section: Resultsmentioning
confidence: 99%